Developments in Multidisciplinary Research and Social Sciences : ISBN 978-606-95069-3-6 - Nemickiene, Živile (Technium Books, 2020)
Developments in Multidisciplinary Research and Social Sciences Volume contains chapters from various researchers in field of Multidisciplinary Research and Social Sciences For citation purposes, cite as indicated below: Developments in Multidisciplinary Research and Social Sciences; ISBN 978-606-95069-3-6, TECHNIUM PRESS: Romania, 2021. Technium Books publish all content in open access, promoting the exchange of ideas and knowledge in a globalized world. Technium Books encompasses all the benefits of open access—high availability and visibility, as well as wide and rapid dissemination. Technium Books are distributed under the terms and conditions of the Creative Commons Attribution License — as an author, you retain the copyright for your work. Technium Books believes that the contemporary wave in academia of wider and faster dissemination of knowledge with open access should not be restricted to academic journals but should also capture and elevate academic & research book publishing. See visitor map: https://clustrmaps.com/site/1bg5q List of Authors Živile Nemickiene - Vilnius University, Kauno kolegija / University of Applied Sciences Kaunas, Lithuania Poenaru Valentina - Constanta Maritime University, Constanta, Romania Novac Valerian - ‘Dunarea de Jos’ University, 47 Domneasca Str., Galati, Romania Bazaitu Razvan - Academia de Politie A. I. Cuza - Bucuresti, Romania Gassim H. Dohal - Gizan, Saudi Arabia Andrei-Ionut Perdum- Polytechnic University of Bucharest, Romania.